Knowledge and Attitude of Faculty Members Working in Dental Institutions towards the Dental Treatment of Patients with HIV/AIDS. (28th October 2014) - Oberoi, Sukhvinder Singh; Sharma, Nilima; Mohanty, Vikrant; Marya, Charumohan; Rekhi, Amit; Oberoi, Avneet
Abstract : Background . Dentists have an ethical responsibility to provide treatment to HIV-infected patients, particularly because oral lesions are common among these patients. However, there are no official guidelines as to how to treat people living with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) (PLWHA) or how to screen for potentially infectious people. Materials and Method . A descriptive cross-sectional questionnaire based study which assessed the knowledge and attitude of the faculty members towards the treatment of patients with HIV/AIDS was carried out in the Sudha Rustagi College of Dental Sciences, Faridabad, and Maulana Azad Institute of Dental Sciences, New Delhi. Results . The willingness to treat patients with HIV was found to be 86.0% among the faculty members in the present study. The majority (79%) of the faculty members thought that treating an HIV-positive patient is ethical responsibility of the dentist. There was a positive attitude (88.0%) among faculty members that routine dental care should be a part of the treatment of patients with HIV/AIDS. Conclusion . The level of knowledge regarding HIV and AIDS was acceptable in the present study. However, continuing dental education (CDE) programmes should be conducted on a regular basis for updating the knowledge level of the faculty members towards the dental treatment of patients with HIV/AIDS patients.